Interface sulfur-coupled hydrogen evolution catalyst, preparation method and application thereof

CN122898909APending Publication Date: 2026-10-13CHINA UNIV OF PETROLEUM (EAST CHINA) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611054880.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]水分子的解离是海水电解阴极析氢反应的速控步骤,但现有的析氢催化剂未能有效调控界面水分子氢键网络,导致强氢键水比例高、自由水比例低,水分子的解离能垒仍然偏高,制约着阴极析氢反应活性的提升;而且,在大电流的工业操作下,阴极产生的大量氢气气泡如果不能快速脱离,会形成“气幕”阻挡催化剂上的活性位点,降低催化活性;此外,天然海水中高浓度的Mg2+、Ca2+在阴极附近因pH升高会形成Mg(OH)2、Ca(OH)2沉淀,现有的析氢催化剂缺乏对电极表面微环境的主动调控能力,导致沉积物逐渐覆盖活性位点,造成电流密度衰减、过电位升高,难以在天然海水中实现数百小时的稳定运行

Benefits of technology

[0017]本发明提供了一种界面硫耦合的析氢催化剂,包括多孔镍基底、负载在所述多孔镍基底上的硫化镍纳米片和负载于所述硫化镍纳米片上的Pt纳米团簇;所述硫化镍纳米片与Pt纳米团簇之间通过硫桥键连接。本发明采用多孔镍作为基底,具有高导电性,而且与NiS晶格匹配度好,有利于硫化镍纳米片在多孔镍基底上原位生长和牢固附着,多孔结构具有高比表面积,可以负载更多的硫化镍纳米片,而且多孔结构有利于电解液的充分渗透和氢气气泡的快速释放。Pt纳米团簇具有量子尺寸效应和独特的配位环境,在析氢反应中的活性和稳定性优于Pt单原子和Pt纳米颗粒。本发明中硫化镍纳米片与Pt纳米团簇之间的界面通过硫耦合,形成强化学键合和电子相互作用,具体体现为硫桥键连接结构。界面硫耦合的结构能够同时调控界面电子结构与海水界面微环境,提高阴极析氢反应活性。首先,硫桥键调控电子结构,使NiS表面形成电子缺位活性位点,并促进吸附氢中间体向Pt位点转移,从而优化氢的吸附与脱附过程;其次,硫桥键能够削弱界面水分子氢键网络,减少强氢键水,提高自由水比例,进而降低水分子的解离能垒,加速水分解动力学;而且,还能够降低气液界面张力促进气泡快速释放,反应过程中气泡的快速释放有助于去除Ca2+和Mg2+沉积物,降低结垢风险,有效抑制Ca2+和Mg2+引发的氢氧化物沉积,提高复杂天然海水环境中催化剂的活性与稳定性。实施例中结果表明,本发明提供的界面硫耦合的析氢催化剂在碱性海水和天然海水体系中均表现出优异的催化活性,可长久稳定运行200h,具有优异的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898909A_ABST
    Figure CN122898909A_ABST
Patent Text Reader

Abstract

The application provides an interface sulfur-coupled hydrogen evolution catalyst and a preparation method and application thereof, and belongs to the technical field of catalytic materials. The hydrogen evolution catalyst comprises a porous nickel substrate, nickel sulfide nanosheets loaded on the porous nickel substrate, and Pt nanoclusters loaded on the nickel sulfide nanosheets; the nickel sulfide nanosheets and the Pt nanoclusters are connected through a sulfur bridge. The sulfur bridge can simultaneously regulate the electronic structure, weaken the hydrogen bond network of interface water molecules, reduce the gas-liquid interfacial tension, promote the rapid release of bubbles, and effectively inhibit Ca 2+ and Mg 2+ hydroxide deposition caused by the bubbles, and improve the activity and stability of the catalyst in a complex natural seawater environment. The interface sulfur-coupled hydrogen evolution catalyst provided by the application exhibits excellent catalytic activity in an alkaline seawater and a natural seawater system, can be stably operated for 200 hours, and has excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic materials technology, specifically relating to an interfacial sulfur-coupled hydrogen evolution catalyst, its preparation method, and its application. Background Technology

[0002] With the increasing demand for green hydrogen energy, direct seawater electrolysis is considered a promising hydrogen production technology due to its ability to utilize abundant and low-cost seawater resources. However, natural seawater contains a large amount of Cl... - Ca 2+ and Mg 2+ Plasma can easily cause problems such as interfacial corrosion, inorganic deposition, and bubble coverage during electrolysis, leading to decreased catalyst activity and reduced stability, which severely restricts the industrial application of direct seawater electrolysis for hydrogen production. In particular, the hydrogen evolution reaction (HER) in the alkaline seawater system requires a water molecule dissociation step first, and the slow water dissociation kinetics are a significant factor limiting HER performance.

[0003] Pt-based materials are widely used in HER catalysis due to their excellent hydrogen adsorption capacity, but they still suffer from insufficient water molecule activation and poor long-term stability in alkaline seawater environments. Existing technologies typically employ multi-component transition metal sulfides to construct heterostructures with Pt, thereby enhancing HER activity by modulating the interfacial electronic structure and synergistic interactions between components.

[0004] The dissociation of water molecules is the rate-determining step of the hydrogen evolution reaction at the cathode in seawater electrolysis. However, existing hydrogen evolution catalysts have failed to effectively regulate the interfacial hydrogen bond network of water molecules, resulting in a high proportion of strongly hydrogen-bonded water and a low proportion of free water. This leads to a still relatively high dissociation energy barrier for water molecules, limiting the improvement of the activity of the hydrogen evolution reaction at the cathode. Furthermore, under high-current industrial operation, if the large amount of hydrogen bubbles generated at the cathode cannot detach quickly, they will form a "gas curtain" that blocks the active sites on the catalyst, reducing catalytic activity. In addition, the high concentration of Mg in natural seawater... 2+ Ca 2+ Near the cathode, Mg(OH)2 and Ca(OH)2 precipitates will form due to the increase in pH. Existing hydrogen evolution catalysts lack the ability to actively regulate the microenvironment on the electrode surface, which leads to the gradual coverage of active sites by deposits, resulting in a decrease in current density and an increase in overpotential, making it difficult to achieve stable operation for hundreds of hours in natural seawater.

[0005] Therefore, developing a hydrogen evolution catalyst that combines high catalytic performance with high stability is of great significance for achieving efficient direct seawater electrolysis to produce hydrogen. Summary of the Invention

[0006] The purpose of this invention is to provide an interfacial sulfur-coupled hydrogen evolution catalyst, its preparation method, and its application. The interfacial sulfur-coupled hydrogen evolution catalyst provided by this invention exhibits both high catalytic performance and high stability in the direct electrolysis of seawater to produce hydrogen.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides an interfacial sulfur-coupled hydrogen evolution catalyst, comprising a porous nickel substrate, nickel sulfide nanosheets supported on the porous nickel substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets; the nickel sulfide nanosheets and the Pt nanoclusters are connected by sulfur bridge bonds.

[0008] Preferably, the loading of the Pt nanoclusters is less than 20%, based on the mass of the nickel sulfide nanosheets.

[0009] Preferably, the valence state of Pt in the Pt nanoclusters is between 0 and +4.

[0010] This invention provides a method for preparing the above-mentioned hydrogen evolution catalyst, comprising the following steps: Porous nickel was first impregnated in a mixed aqueous solution of nickel salt and hydride, then removed and secondly impregnated in an aqueous solution of platinum salt to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

[0011] Preferably, the nickel ion concentration in the mixed aqueous solution of the nickel salt and hydrosulfide is 0.1~0.8 mol / L, and the hydrosulfide ion concentration is 0.03~0.8 mol / L.

[0012] Preferably, the first immersion time is 10 to 40 minutes.

[0013] Preferably, the concentration of platinum ions in the platinum salt aqueous solution is 0.001~0.02 mol / L.

[0014] Preferably, the second immersion time is 30 to 120 minutes.

[0015] Preferably, the porous nickel is pretreated before use; the pretreatment includes: ultrasonically treating the porous nickel sequentially in 0.05~0.2mol / L hydrochloric acid solution, analytical grade acetone and anhydrous ethanol, and then drying it.

[0016] This invention provides the application of the above-mentioned interfacial sulfur-coupled hydrogen evolution catalyst in seawater electrolysis for hydrogen production.

[0017] This invention provides a sulfur-coupled hydrogen evolution catalyst, comprising a porous nickel substrate, nickel sulfide nanosheets supported on the porous nickel substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets; the nickel sulfide nanosheets and Pt nanoclusters are connected by sulfur bridge bonds. The porous nickel substrate used in this invention has high conductivity and good lattice matching with NiS, which is beneficial for the in-situ growth and firm attachment of nickel sulfide nanosheets on the porous nickel substrate. The porous structure has a high specific surface area, allowing for the loading of more nickel sulfide nanosheets, and also facilitates sufficient electrolyte penetration and rapid release of hydrogen bubbles. Pt nanoclusters possess quantum size effects and a unique coordination environment, exhibiting superior activity and stability in the hydrogen evolution reaction compared to single Pt atoms and Pt nanoparticles. In this invention, the interface between the nickel sulfide nanosheets and Pt nanoclusters is coupled by sulfur, forming strong chemical bonds and electronic interactions, specifically manifested as a sulfur bridge bond connection structure. The sulfur-coupled structure can simultaneously regulate the interfacial electronic structure and the seawater interfacial microenvironment, improving the activity of the cathode hydrogen evolution reaction. First, sulfur bridges regulate the electronic structure, creating electron-vacant active sites on the NiS surface and promoting the transfer of adsorbed hydrogen intermediates to Pt sites, thereby optimizing the hydrogen adsorption and desorption process. Second, sulfur bridges weaken the interfacial hydrogen bond network of water molecules, reducing strongly hydrogen-bonded water and increasing the proportion of free water, thus lowering the dissociation energy barrier of water molecules and accelerating water splitting kinetics. Furthermore, they reduce the gas-liquid interfacial tension, promoting rapid bubble release, which helps remove Ca during the reaction. 2+ and Mg 2+ Deposits reduce the risk of scaling and effectively inhibit calcium deposition. 2+ and Mg 2+ The induced hydroxide deposition enhances the activity and stability of the catalyst in complex natural seawater environments. The results in the examples demonstrate that the interfacial sulfur-coupled hydrogen evolution catalyst provided by this invention exhibits excellent catalytic activity in both alkaline and natural seawater systems, and can operate stably for 200 hours, demonstrating excellent stability. Attached Figure Description

[0018] Figure 1 This is a SEM image of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 2 The XRD pattern of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 3 The image shows the HRTEM image of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1. Figure 4 The X-ray absorption near-edge structure spectrum of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 5 This is an extended X-ray absorption fine structure spectrum of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 6 The in-situ Raman spectrum of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 7 The graph shows the performance test results of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1 under alkaline seawater conditions. Figure 8 This is a two-electrode stability test diagram of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1; Figure 9 The graph shows the performance test results of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 1 under natural seawater conditions. Figure 10 The graph shows the performance test results of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 2 under alkaline seawater conditions. Figure 11 The graph shows the performance test results of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in Example 3 under alkaline seawater conditions. Figure 12 This is a graph showing the performance test results of a commercial Pt / C catalyst under alkaline seawater conditions. Detailed Implementation

[0019] This invention provides an interfacial sulfur-coupled hydrogen evolution catalyst, comprising a porous nickel substrate, nickel sulfide nanosheets supported on the porous nickel substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets; the nickel sulfide nanosheets and the Pt nanoclusters are connected by sulfur bridge bonds.

[0020] The interfacial sulfur-coupled hydrogen evolution catalyst provided by this invention comprises a porous nickel substrate. In this invention, the porous nickel substrate provides the structural basis for the growth of nickel sulfide nanosheets and the loading of Pt nanoclusters. Metallic nickel and NiS have good lattice matching, allowing NiS to grow in situ on the nickel surface and form a strong adhesion, thereby enhancing the bonding force between the NiS nanosheets and the porous nickel substrate, preventing detachment during long-term operation, and improving stability. Furthermore, metallic nickel itself has excellent conductivity, enabling rapid transfer of electrons from the external circuit to the catalyst's active sites, while effectively discharging the current generated by the reaction, thus improving energy efficiency. The porous structure has a high specific surface area, which can increase the loading of nickel sulfide nanosheets and Pt nanoclusters, thereby increasing the density of active sites. Moreover, the porous structure facilitates rapid electrolyte penetration and the rapid release of generated hydrogen bubbles, preventing bubble retention and blockage of active sites.

[0021] In one embodiment of the present invention, the porous nickel substrate may be nickel foam, and the porosity of the nickel foam is preferably 95% to 98%.

[0022] The interfacial sulfur-coupled hydrogen evolution catalyst provided by this invention further includes nickel sulfide nanosheets supported on the porous nickel substrate. In this invention, the nickel sulfide nanosheets serve as a carrier for Pt nanoclusters and provide a structural basis for the formation of sulfur bridges.

[0023] The interfacial sulfur-coupled hydrogen evolution catalyst provided by this invention further includes Pt nanoclusters supported on the nickel sulfide nanosheets. In this invention, the Pt nanoclusters are the main catalytic centers. Pt nanoclusters possess quantum size effects and unique coordination environments, exhibiting superior activity and stability in the hydrogen evolution reaction compared to single Pt atoms and Pt nanoparticles.

[0024] In this invention, the nickel sulfide nanosheets and Pt nanoclusters are connected by sulfur bridges. The S atoms in NiS have lone pairs of electrons, forming Pt-S bonds with the Pt atoms in the Pt nanoclusters, thus constructing a sulfur bridge connection structure. The strong chemical bonding of the sulfur bridge effectively anchors the Pt nanoclusters, preventing their migration and detachment, and improving long-term stability. The sulfur bridge can regulate the electronic structure, creating electron-deficient active sites on the NiS surface and promoting the transfer of adsorbed hydrogen intermediates to Pt sites, thereby optimizing the hydrogen adsorption and desorption process. Furthermore, the sulfur bridge weakens the interfacial hydrogen bond network, reducing the proportion of ordered, difficult-to-dissociate strongly hydrogen-bonded water and increasing the proportion of disordered, easily dissociated free water, lowering the dissociation energy barrier of water molecules, and thus accelerating water splitting kinetics. In addition, the sulfur bridge regulation reduces the gas-liquid interfacial tension, making it easier for the generated hydrogen bubbles to merge, grow, and detach rapidly, reducing the loss of active sites caused by bubble coverage. Simultaneously, the rapid release of the bubbles can also physically flush away Ca. 2+ and Mg 2+ Deposits reduce the risk of scaling.

[0025] In this invention, based on the mass of nickel sulfide nanosheets, the loading of the Pt nanoclusters is preferably less than 20%, more preferably 10-20%. A loading of less than 20% is beneficial for Pt to be highly dispersed on the NiS surface in the form of nanoclusters, avoiding the migration and aggregation of Pt atoms to form large particles due to excessive loading, thereby maintaining high atomic utilization and high active sites; moreover, a loading of less than 20% is beneficial for most Pt atoms in the Pt nanoclusters to participate in the formation of sulfur bridges, thereby improving the formation efficiency of sulfur bridges.

[0026] In this invention, the valence state of Pt in the Pt nanoclusters is preferably between 0 and +4. The Pt in the Pt nanoclusters is neither in a fully metallic state (0 valence) nor a fully oxidized state (+4 valence); its valence state is between 0 and +4, representing a partially oxidized state. This indicates the presence of interfacial electron transfer forming sulfur bridges. This interfacial electron transfer optimizes the d-band center of Pt, making it most favorable for hydrogen generation and desorption, thus improving intrinsic catalytic activity.

[0027] In this invention, the interface between nickel sulfide nanosheets and Pt nanoclusters in the sulfur-coupled hydrogen evolution catalyst exhibits strong chemical bonding and electronic interactions through sulfur coupling, specifically manifested as a sulfur bridge bond structure. This sulfur-coupled structure can simultaneously regulate the interfacial electronic structure and the seawater interfacial microenvironment, enhancing the activity of the cathode hydrogen evolution reaction. First, the sulfur bridge bond regulates the electronic structure, creating electron-deficient active sites on the NiS surface and promoting the transfer of adsorbed hydrogen intermediates to Pt sites, thereby optimizing the hydrogen adsorption and desorption process. Second, the sulfur bridge bond weakens the interfacial water molecule hydrogen bond network, reducing strongly hydrogen-bonded water and increasing the proportion of free water, thus lowering the dissociation energy barrier of water molecules and accelerating water splitting kinetics. Furthermore, it reduces the gas-liquid interfacial tension, promoting rapid bubble release, which aids in the removal of Ca during the reaction. 2+ and Mg 2+ Deposits reduce the risk of scaling and effectively inhibit calcium deposition. 2+ and Mg 2+ The induced hydroxide deposition enhances the activity and stability of the catalyst in complex natural seawater environments.

[0028] This invention also provides a method for preparing the interfacial sulfur-coupled hydrogen evolution catalyst described in the above technical solution, comprising the following steps: Porous nickel was first impregnated in a mixed aqueous solution of nickel salt and hydride, then removed and secondly impregnated in an aqueous solution of platinum salt to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

[0029] The present invention does not have any special limitation on the source of the raw materials, and commercially available products known to those skilled in the art can be used.

[0030] In one embodiment of the present invention, the porous nickel can be nickel foam.

[0031] In this invention, the porous nickel is preferably pretreated before use; the pretreatment preferably includes: ultrasonically treating the porous nickel sequentially in 0.05~0.2 mol / L hydrochloric acid solution, analytical grade acetone, and anhydrous ethanol, followed by drying. This pretreatment of the porous nickel removes surface organic matter and oxides, which is beneficial for the in-situ growth and firm adhesion of NiS.

[0032] In one embodiment of the present invention, the nickel salt may be nickel chloride, and the hydrosulfide may be sodium hydrosulfide.

[0033] In this invention, the nickel ion concentration in the mixed aqueous solution of nickel salt and hydrosulfide is preferably 0.1~0.8 mol / L, more preferably 0.1~0.5 mol / L; the hydrosulfide ion concentration in the mixed aqueous solution of nickel salt and hydrosulfide is 0.03~0.8 mol / L, more preferably 0.07~0.4 mol / L.

[0034] The present invention does not have special requirements for the preparation method of the mixed aqueous solution of nickel salt and hydrosulfide; the raw materials can be mixed using a mixing method well known to those skilled in the art. As one embodiment of the present invention, the nickel salt and hydrosulfide can be mixed and then dissolved in water to obtain the solution.

[0035] In this invention, the mixed aqueous solution of nickel salt and hydride is preferably prepared before use. The precipitation reaction between nickel ions and hydride ions to form NiS precipitate requires two stages: nucleation and growth. In a homogeneous solution system, precipitation needs to overcome the nucleation energy barrier; when the ion concentration product just exceeds the solubility product, a high degree of supersaturation is required for spontaneous nucleation. This invention controls the concentrations of nickel ions and hydride ions, keeping the mixed aqueous solution of nickel salt and hydride in a supersaturated but non-nucleated metastable state, thus preventing the formation of NiS precipitate in the solution.

[0036] In this invention, the first impregnation time is preferably 10-40 min, more preferably 10-30 min. The first impregnation temperature is preferably room temperature. In this invention, during the first impregnation, porous nickel is immersed in a mixed aqueous solution of nickel salt and hydrosulfide. The porous nickel matches the NiS crystal structure, providing low-energy-barrier nucleation sites for NiS, allowing NiS to preferentially nucleate and grow heterogeneously on the surface of the nickel foam, rather than forming a precipitate in the solution. At room temperature, the reaction rate of the precipitation reaction between nickel ions and hydrosulfide ions in the solution to form NiS precipitate is slow, and NiS precipitate will not preferentially form in the solution. By controlling the first impregnation time and temperature, this invention can better control the degree of NiS nucleation and growth on the porous nickel substrate.

[0037] After the first impregnation is completed, the present invention preferably removes the obtained product, rinses it with deionized water and ethanol, dries it, and then performs the second impregnation.

[0038] In one embodiment of the present invention, the platinum salt in the platinum salt aqueous solution can be H2PtCl6·6H2O.

[0039] In this invention, the platinum ion concentration in the platinum salt aqueous solution is 0.001~0.02 mol / L. Controlling the platinum ion concentration allows for better control of the formation and loading of Pt nanoclusters.

[0040] In this invention, the second impregnation time is preferably 30-120 min, more preferably 30-60 min. The second impregnation temperature is preferably room temperature. During the second impregnation process, platinum ions first accumulate on the surface of nickel sulfide nanosheets through electrostatic or chemisorption. Then, sulfur atoms in NiS partially reduce the platinum ions, and the reduced Pt atoms aggregate on the NiS surface to form Pt nanoclusters. Simultaneously, Pt-S chemical bonds are formed between Pt and NiS. Controlling the second impregnation time in this invention allows for better generation of Pt nanoclusters and sulfur bridges.

[0041] This invention uses a two-step impregnation method at room temperature, which is simple and mild.

[0042] This invention provides the application of the above-mentioned interfacial sulfur-coupled hydrogen evolution catalyst in seawater electrolysis for hydrogen production.

[0043] In one embodiment of the present invention, the interfacial sulfur-coupled hydrogen evolution catalyst can perform electrolytic hydrogen evolution in alkaline seawater. In an embodiment of the present invention, the area of ​​the interfacial sulfur-coupled hydrogen evolution catalyst is 2 cm². 2 The electrolyte for the electrolytic hydrogen evolution is alkaline seawater with a KOH concentration of 1 mol / L. The working electrode is a hydrogen evolution catalyst coupled with interfacial sulfur, the counter electrode is a carbon rod, and the reference electrode is a Hg / HgO electrode. The three electrodes are assembled at room temperature to carry out the electrolytic hydrogen evolution reaction.

[0044] As one embodiment of the present invention, the interfacial sulfur-coupled hydrogen evolution catalyst can also perform electrolytic hydrogen evolution under natural seawater conditions. In an embodiment of the present invention, the area of ​​the interfacial sulfur-coupled hydrogen evolution catalyst is 2 cm². 2 The electrolyte for the electrolytic hydrogen production is natural seawater. The hydrogen production is carried out by seawater electrolysis in an anion exchange membrane electrolyzer. The interfacial sulfur-coupled hydrogen evolution catalyst serves as the cathode, and the sulfur-doped nickel-iron layered double hydroxide S-NiFe LDH serves as the anode. The electrolytic hydrogen production reaction is carried out under temperature control of 70~75℃.

[0045] As one embodiment of the present invention, the current density during the electrolytic hydrogen removal under natural seawater conditions can be no less than 500 mA·cm⁻¹. 2- Industrial current density.

[0046] The interfacial sulfur-coupled hydrogen evolution catalyst of this invention exhibits good stability and catalytic performance at industrial current densities.

[0047] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0048] Example 1 A hydrogen evolution catalyst with interfacial sulfur coupling consists of a nickel foam substrate, nickel sulfide nanosheets supported on the nickel foam substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets, wherein the porosity of the nickel foam is 95%.

[0049] The preparation method is as follows: (1) Cut the nickel foam into 1cm×2cm pieces, immerse them in 60mL of 0.1mol / L hydrochloric acid solution, 60mL of analytical grade acetone and 60mL of anhydrous ethanol in sequence, sonicate for 15min, and then dry them in a vacuum oven to obtain the treated nickel foam.

[0050] (2) Mix 0.2g NiCl2 and 0.05g NaHS and dissolve them in 5 mL of water to form a solution. Immerse the foamed nickel treated in step (1) in the solution for 30 min. After taking it out, rinse it with deionized water and ethanol and dry it.

[0051] (3) The product obtained in step (2) was immersed in 10 mL of a solution containing 36 mg H2PtCl6·6H2O at room temperature for 60 min, and then dried to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

[0052] The interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment was observed using scanning electron microscopy, and the SEM images are shown below. Figure 1 As shown, the nickel sulfide nanosheets in the hydrogen evolution catalyst exhibit a nanospindle morphology.

[0053] The interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment was tested using X-ray diffraction, and the XRD pattern is shown below. Figure 2 As shown, the NiS crystalline phase can be seen in the hydrogen evolution catalyst.

[0054] The interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment was observed using high-resolution transmission electron microscopy, and the HRTEM image is shown below. Figure 3 As shown, the lattice fringes of NiS and Pt nanoclusters can be clearly observed.

[0055] X-ray absorption fine structure spectroscopy was used to analyze Pt foil standards, PtO2 standards, and the interfacial sulfur-coupled hydrogen evolution catalyst in this example. The X-ray absorption near-edge structure spectra are shown below. Figure 4As shown. The tests were conducted at the BL14W1 hard XAFS beamline of the Shanghai Synchrotron Radiation Facility. The Pt foil and PtO2 standard spectra used in the tests were provided by the testing service provider and were archived standard reference samples retained by the beamline. The test conditions were completely consistent. By comparison, it can be seen that the valence state of Pt in the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment is between 0 and +4, indicating that electron transfer occurred in the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment, and the electronic structure of Pt was modulated.

[0056] X-ray absorption fine structure spectroscopy was used to analyze Pt foil standards, PtO2 standards, and the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment. The extended X-ray absorption fine structure spectra are shown below. Figure 5 As shown. The tests were performed at the BL14W1 hard XAFS beamline of the Shanghai Synchrotron Radiation Facility. The spectra of the Pt foil and PtO2 standards used in the tests were provided by the testing service provider and were archived standard reference samples retained by the beamline. The test conditions were completely consistent. By comparison, it can be seen that Pt-S bonds were formed in the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment, indicating the presence of sulfur bridge bonds in the hydrogen evolution catalyst.

[0057] The interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment was analyzed using in-situ Raman spectroscopy, and the in-situ Raman spectra were obtained as follows: Figure 6 As shown. The left figure shows the Raman water peak of the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment, and the right figure shows a comparison of the peak ratios of 2-coordinated water (2-HBW) and free water (KW) of the interfacial sulfur-coupled hydrogen evolution catalyst in this embodiment and commercial Pt / C. The peaks can be viewed in the range of 3000~3750 cm⁻¹. -1 A distinct water peak was observed at this location. By analyzing the peak, it was found that the peak was at 3450 cm⁻¹. -1 The strength of the strong hydrogen bonds in water decreases significantly around 3600 cm⁻¹, while at 3600 cm⁻¹... -1 The significantly increased proportion of free water indicates that the sulfur bridge bond modulates the hydrogen bond network by regulating the electronic structure during the hydrogen evolution reaction at the cathode, thus promoting hydrogen production.

[0058] The performance of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was tested. The specific procedures were as follows: The electrolyte was seawater with a KOH concentration of 1 mol / L, obtained by filtering out microorganisms and sediment from seawater obtained at Qingdao Shilaoren Bathing Beach before adding KOH. The performance test results are shown in the figure below. Figure 7 As shown, the X-axis represents the operating voltage (V), and the Y-axis represents the current density (mA·cm). -2 ), achieving 500 mA·cm requires only 133 mV overpotential. -2 The current density indicates that the hydrogen evolution catalyst has excellent HER activity.

[0059] The interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was subjected to a two-electrode stability test. The specific operation was as follows: the electrolyte was seawater with a KOH concentration of 1 mol / L. The interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was used as the cathode, and S-NiFe LDH was used as the anode in an electrolytic cell. The performance was tested using a chronopotential (ut) method, and the resulting performance test graph is shown below. Figure 8 As shown, the X-axis represents the operating voltage (V), and the Y-axis represents the current density (mA·cm). -2 It can be seen that under alkaline seawater conditions, the hydrogen evolution catalyst can operate stably for 200 hours, demonstrating excellent stability.

[0060] The performance of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was tested. The specific procedures were as follows: Natural seawater was used as the electrolyte, and the seawater was taken from Shilaoren Beach in Qingdao, Shandong Province. The hydrogen evolution catalyst obtained in this embodiment was used as the cathode of an anion exchange membrane electrolyzer, and S-NiFe LDH was used as the anode. Hydrogen production was carried out by seawater electrolysis in the anion exchange membrane electrolyzer. The performance test results are shown in the figure below. Figure 9 As shown, it can be seen that at 1.0 A·cm -2 It can operate stably for more than 200 hours at current densities, demonstrating excellent stability.

[0061] Example 2 A hydrogen evolution catalyst with interfacial sulfur coupling consists of a nickel foam substrate, nickel sulfide nanosheets supported on the nickel foam substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets, wherein the porosity of the nickel foam is 95%.

[0062] The preparation method is as follows: (1) Cut the nickel foam into 1cm×2cm pieces, immerse them in 50mL of 0.1mol / L hydrochloric acid solution, 50mL of analytical grade acetone and 50mL of anhydrous ethanol in sequence, sonicate for 20min, and then dry them in a vacuum oven to obtain the treated nickel foam.

[0063] (2) Mix 0.1g NiCl2 and 0.02g NaHS and dissolve them in 5 mL of water to form a solution. Immerse the foamed nickel treated in step (1) in the solution for 30 min. After taking it out, rinse it with deionized water and ethanol and dry it.

[0064] (3) The product obtained in step (2) was immersed in 10 mL of a solution containing 36 mg H2PtCl6·6H2O at room temperature for 60 min, and then dried to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

[0065] The performance of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was tested. The specific operation was as follows: using the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment as the working electrode, the carbon rod as the counter electrode, and the Hg / HgO reference electrode as the three-electrode configuration, the test was conducted in an electrolytic cell containing seawater with a KOH concentration of 1 mol / L. The performance test results are shown in the figure below. Figure 10 As shown, the X-axis represents the operating voltage (V), and the Y-axis represents the current density (mA·cm). -2 This shows that the hydrogen evolution catalyst has excellent HER activity.

[0066] Example 3 A hydrogen evolution catalyst with interfacial sulfur coupling consists of a nickel foam substrate, nickel sulfide nanosheets supported on the nickel foam substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets, wherein the porosity of the nickel foam is 95%.

[0067] The preparation method is as follows: (1) Cut the nickel foam into 1cm×2cm pieces, immerse them in 50mL of 0.1mol / L hydrochloric acid solution, 50mL of analytical grade acetone and 50mL of anhydrous ethanol in sequence, sonicate for 25min, and then dry them in a vacuum oven to obtain the treated nickel foam.

[0068] (2) Mix 0.3g NiCl2 and 0.1g NaHS and dissolve them in 5 mL of water to form a solution. Immerse the foamed nickel treated in step (1) in the solution for 30 min. After taking it out, rinse it with deionized water and ethanol and dry it.

[0069] (3) The product obtained in step (2) was immersed in 10 mL of a solution containing 36 mg H2PtCl6·6H2O at room temperature for 60 min, and then dried to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

[0070] The performance of the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment was tested. The specific operation was as follows: using the interfacial sulfur-coupled hydrogen evolution catalyst obtained in this embodiment as the working electrode, the carbon rod as the counter electrode, and the Hg / HgO reference electrode as the three-electrode configuration, the test was conducted in an electrolytic cell containing seawater with a KOH concentration of 1 mol / L. The performance test results are shown in the figure below. Figure 11 As shown, the X-axis represents the operating voltage (V), and the Y-axis represents the current density (mA·cm). -2 This shows that the hydrogen evolution catalyst has excellent HER activity.

[0071] Comparative Example 1 The hydrogen evolution catalyst used in this comparative example was a commercial Pt / C catalyst, purchased from Alfa Isa (China) Chemical Co., Ltd., model number 047381.03-1g. Performance testing was conducted under alkaline seawater conditions. The specific procedure was as follows: a three-electrode system was used, consisting of the commercial Pt / C catalyst as the working electrode, a carbon rod as the counter electrode, and an Hg / HgO reference electrode. The test was performed in an electrolytic cell containing seawater with a KOH concentration of 1 mol / L. The performance test results are shown in the figure below. Figure 12 As shown, the X-axis represents the operating voltage (V), and the Y-axis represents the current density (mA·cm). -2 Compared with Example 1, it has a larger negative operating voltage and lower HER activity.

[0072] As can be seen from the above examples and comparative examples, the interfacial sulfur-coupled hydrogen evolution catalyst provided by the present invention has high activity and high stability.

[0073] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A hydrogen evolution catalyst with interfacial sulfur coupling, characterized in that, It includes a porous nickel substrate, nickel sulfide nanosheets supported on the porous nickel substrate, and Pt nanoclusters supported on the nickel sulfide nanosheets; the nickel sulfide nanosheets and Pt nanoclusters are connected by sulfide bridge bonds.

2. The hydrogen evolution catalyst according to claim 1, characterized in that, Based on the mass of nickel sulfide nanosheets, the loading of the Pt nanoclusters is less than 20%.

3. The hydrogen evolution catalyst according to claim 1 or 2, characterized in that, The valence state of Pt in the Pt nanoclusters is between 0 and +4.

4. A method for preparing an interfacial sulfur-coupled hydrogen evolution catalyst, characterized in that, Includes the following steps: Porous nickel was first impregnated in a mixed aqueous solution of nickel salt and hydride, then removed and secondly impregnated in an aqueous solution of platinum salt to obtain an interfacial sulfur-coupled hydrogen evolution catalyst.

5. The preparation method according to claim 4, characterized in that, The nickel ion concentration in the mixed aqueous solution of the nickel salt and hydrosulfide is 0.1~0.8 mol / L, and the hydrosulfide ion concentration is 0.03~0.8 mol / L.

6. The preparation method according to claim 4, characterized in that, The first immersion time is 10-40 minutes.

7. The preparation method according to claim 4, characterized in that, The concentration of platinum ions in the platinum salt aqueous solution is 0.001~0.02 mol / L.

8. The preparation method according to claim 4, characterized in that, The second immersion time is 30~120 minutes.

9. The preparation method according to claim 4, characterized in that, The porous nickel is pretreated before use; the pretreatment includes: ultrasonically treating the porous nickel in 0.05~0.2mol / L hydrochloric acid solution, analytical grade acetone and anhydrous ethanol in sequence, and then drying it.

10. The application of the interfacial sulfur-coupled hydrogen evolution catalyst according to claims 1 to 3 or the interfacial sulfur-coupled hydrogen evolution catalyst prepared by the preparation method according to any one of claims 4 to 9 in seawater electrolysis for hydrogen production.